A novel fog-based resource allocation policy for vehicular clouds in the highway environment - Pereira, Rickson S. [UNESP]; Lieira, Douglas D.; Silva, Marco A. C. da; Pimenta, Adinovam H. M.; Cost, Joahannes B. D. da; Rosario, Denis; Meneguette, Rodolfo I.; Gutierrez, C. A. (Ieee, 2019)
Vehicular networks has unique characteristics compared to other wireless networks, such as, highly dynamic topology, short transmission time, among others. These characteristics becomes a challenge for management and allocation of vehicle cloud resources. In this paper, we propose a allocatioN and mANgement resourCe policY for vehicular cloud, called of NANCY. For this, we formulate the problem of allocation of resources through the mathematical method Multiple Attribute Decision, which will decide whether NANCY will allocate the resources available to attend or not the service requested by the vehicle. Simulation results showed that NANCY provides a larger amount of service to be provided, providing a reduction in the number of service locks due to its accuracy, as well as a reduction in the amount of services discarded due to its load balancing in resource allocation.
Keywords: fog; resource allocation; vehicular cloud